P.036 Exploring changes in functional connectivity after a first unprovoked seizure: an fMRI resting state and movie-driven data study. (June 2022) - Paredes-Aragón, EM; Mofrad, M; Busch, A; Kahn, A; Johnsrude, I; Muller, L; Mirsattari, S
Abstract : Background: A single unprovoked seizure occurs in up to 10% of patients, but does not necessarily develop into epilepsy. It is unclear what determines the susceptibility to develop epilepsy. Although brain network changes have been ascertained in people with epilepsy, this field has not been studied in single seizure patients. Methods: Using 7T resting-state fMRI scanning, and co-registration watching a movie for naturalistic analysis of functional connectivity (Fc). Whole brain, Fc and Brodmann areas were analyzed using phase similarity measures and graph theory. Results: Ten patients with a single unprovoked seizure and fourteen age-and sex-matched healthy controls were recruited. Baseline characteristics were similar. Fc at baseline had no differences between groups. Movie-driven analysis did not show a significant difference overall regions but we observed significant differences in default mode and Visual association cortex as well as Dorsal posterior cingulate cortex (Dorsal PCC). Conclusions: Although no network connectivity differences were found between patients and controls, when movie-driven data was analyzed, differences were seen when comparing patients in the default mode network, visual association cortex, and dorsal posterior cingulate.